Psychological determinants of the use of complementary and alternative medicine – CAM - Księska-Koszałka, Joanna (Journal of Education, Health and Sport, 2021)
Introduction and purpose. Today, there is a growing popularity of complementary and alternative medicine (CAM). The phenomenon is based on a number of conditions that are of interest to social sciences. These studies encounter a number of methodological difficulties. The aim of the article is to present the psychological determinants of CAM application in the light of the literature on the subject. The presentation of the state of knowledge was preceded by an extensive theoretical introduction due to the scarcity of current Polish studies on the discussed subject in the literature on health psychology. A review of research works from 1990-2021 in databases available on Ebsco resources, i.e. Medline, APA PsycArticles, APA PsycInfo, CINAHL; in the Google Scholar search engine; literature lists of found articles and in own resources. Brief description of knowledge. There are relatively few existing studies on this phenomenon, and the results of the studies to date are often contradictory. The best-known determinants of CAM use are environmental and cognitive factors related to cognitive styles and beliefs. Factors related to spirituality and religiosity are also of great importance. Least is known about personality and emotional factors. Summary. The subject of psychological determinants of CAM application requires further research. A deeper understanding of the determinants of the phenomenon will allow for a better understanding of the needs and expectations of patients that underlie health attitudes.